AKIBAT HAK ASUH ANAK DI BAWAH UMUR YANG DIASUH TERPISAH OLEH AYAH ATAU IBU PASCA PERCERAIAN (STUDI KASUS: PUTUSAN PENGADILAN NEGERI TABANAN NOMOR: 169/PDT.G/2017/PN.TAB) - Verronica Verronica; Imelda Martinelli (Fakultas Hukum Universitas Tarumanagara, 2022)
Divorce ends the relationship between husband and wife, but does not apply to the relationshipbetween parents and children. Children have their rights, including for minors. Positive law hasregulated the rules in taking care of children after divorce with the stipulation as the holder of childcustody from the court. The rules have been clearly stated in various laws, there are also customarylaws that regulate people's lives in various regions so that this should be taken into consideration ifyou want to separate child custody. What are the consequences for the custody of minors who arecared for separately by the father or mother after the divorce? The author examines this problemusing normative legal research methods. The research data shows that the judge's decision to separatethe custody of minors had a bad impact on one of the children from the point of view of Balinesecustomary law, but not when viewed from the rules in positive law. This is because Balinese customarylaw adheres to the Patrilineal kinship system (following the father's lineage). Therefore, it is highlyexpected that child custody is fully given to the father who has good behavior so that their children donot experience confusion that makes it dif icult for them to obtain their rights for having their mother’saf ection. The judge's decision should involve the customary law that applies in the community as aconsideration in determining child custody rights so they will not suf er losses to the rights they have.